Dithiocarb (N, N‐diethyldithiocarbamate, DEDTC) decreases levels of biogenic monoamines in the adult mouse brain. Issue 6 (October 2014) - Redondo‐Castro, Elena; Romero, Rafael; Torres‐Espín, Abel; Utrera, Juana; Duque, Daniel; Junyent, Fèlix; Auladell, Carme
<x xml:space="preserve">Abstract</x> Aims Dithiocarb (diethyldithiocarbamate, DEDTC) belongs to the group of dithiocarbamates and is the main metabolite of disulphiram, a drug of choice for the treatment of alcohol dependence. Its therapeutic potential relays on its ability to create an unpleasant aversive reaction following the ingestion of alcohol, and this effect is usually accompanied by neurobehavioural symptoms. Most of these can be attributed to the impaired metabolism of brain biogenic amines. Methods To gain new insights into the dithiocarbamates and their effects on neurotransmitter systems, an in vivo experimental model based on daily injections of DEDTC in adult mice for 7 days was established. To this end, the concentrations of the three major brain monoamines, dopamine (DA), noradrenaline (NA) and serotonin (5‐HT) were measured in whole brain extracts with high‐performance liquid chromatography (HPLC). The levels of D2 dopamine receptor (D2R) were evaluated by Western blot and by immunohistochemical techniques the cell pattern of tyrosine hydroxylase (TH), dopa beta hydroxylase (DBH) and choline acetyltransferase ChAT) were analysed. Results A significant reduction in DA and 5‐HT levels was observed, whereas NA was not affected. Moreover, decreases in D2R levels, as well as in enzymes such as TH, DBH and ChAT, were found. Conclusions Our data suggest that DEDTC provokes alterations in biogenic amines and in different substrates of neurotransmitter systems, which could explain some of the neurobehavioural effects observed in patients treated with disulphiram.